Respuesta :
From point A to C, which is the length of the entire line, it's 3x + 1.
AB = 2x + 4
BC = 10
This means that AB + BC = AC
All you have to do is plug in the equations.
(2x + 4) + (10) = (3x + 1)
2x + 14 = 3x + 1
2x + 13 = 3x
13 = x
Now plug in the value of x (13) into the AC equation (3x + 1).
AC = 3(13) + 1
AC = 39 + 1
AC = 40
The answer is:
a. 40
AB = 2x + 4
BC = 10
This means that AB + BC = AC
All you have to do is plug in the equations.
(2x + 4) + (10) = (3x + 1)
2x + 14 = 3x + 1
2x + 13 = 3x
13 = x
Now plug in the value of x (13) into the AC equation (3x + 1).
AC = 3(13) + 1
AC = 39 + 1
AC = 40
The answer is:
a. 40